The Ability of Triple Antibiotic Paste and Calcium Hydroxide in Disinfection of Dentinal Tubules - Adl, Alireza; Hamedi, Sabie; Motamedifar, Mohamad; Sobhnamayan, Fereshte (Iranian Endodontic Journal, 2014)
Introduction: The purpose of this in vitro study was to compare the ability of triple antibiotic paste (TAP) to calcium hydroxide (CH) in disinfecting dentinal tubules. Material and Methods: Sixty root blocks were obtained from extracted single-rooted human teeth. The root canals were enlarged with Gates-Glidden drills up to size 3 and were contaminated with Enterococcus. faecalis (E. faecalis), and then left for 21 days. The contaminated blocks were treated with saline (as negative control), CH or TAP. Dentin debris was obtained at the end of first and 7th days, using Gates-Glidden drills sizes 4 and 5 from two different depths of 100 and 200 µm. The vital bacterial load was assessed by counting the number of colony forming units (CFUs). The data was analyzed with the Kruskal-Wallis H and Dunn Post-Hoc tests. The Wilcoxon Signed Ranks test was used to check for differences in bacterial growth at both depths (P<0.05). Results: In comparison with CH, the TAP significantly decreased the number of CFUs in both depths and time intervals (P<0.001), while the CH group showed a moderate antibacterial effect. Conclusion: TAP is more effective in disinfecting the canal against E. faecalis compared to CH.